2015
DOI: 10.1161/strokeaha.115.009076
|View full text |Cite
|
Sign up to set email alerts
|

Day-by-Day Blood Pressure Variability and Functional Outcome After Acute Ischemic Stroke

Abstract: Therefore, BP variability in both the acute and subacute stages Background and Purpose-The relationship between blood pressure (BP) variability and functional outcome in patients with acute ischemic stroke remains unclear. This study aimed to elucidate whether in-hospital day-by-day BP variability is associated with functional outcome after acute ischemic stroke. Methods-Using the Fukuoka Stroke Registry, we included 2566 patients with a first-ever ischemic stroke who had been functionally independent before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…Only a few reports on the relationship between BP variability during the subacute stage of AIS and stroke outcomes are available, in contrast to several reports on BP fluctuation in the acute phase. Previous reports suggested that BP variability during the subacute stage was associated with functional outcome at 3 months after stroke onset, independent of mean BP level 22,23 . In the present study, BP variability, but not average BP, during the subacute stage of ischemic stroke was significantly associated with poor outcomes at 3 months in the multivariable analysis, as previously reported 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Only a few reports on the relationship between BP variability during the subacute stage of AIS and stroke outcomes are available, in contrast to several reports on BP fluctuation in the acute phase. Previous reports suggested that BP variability during the subacute stage was associated with functional outcome at 3 months after stroke onset, independent of mean BP level 22,23 . In the present study, BP variability, but not average BP, during the subacute stage of ischemic stroke was significantly associated with poor outcomes at 3 months in the multivariable analysis, as previously reported 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies mostly enrolled blood pressure patients and their results are the reflection of association between BPV and secondary or primary stroke prevention [24][25][26]. Currently, there are few prospective studies [9,27,28] had focused on the relationship between BPV and SIP. Ishituska et al [29] had found that patients with average SBP ≥ 166 mmHg had higher rate of SIP compared with patients with average SBP ≤ 132 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Fukuda et al assessed the relationship between the in-hospital day-by-day blood pressure variability during the acute and subacute stage of ischemic stroke and poor functional outcome at 3 months [52]. They included 2566 patients with acute ischemic stroke and measured BP daily as well as its variability (defined as SD, CV, and VIM).…”
Section: Short-term Blood Pressure Variabilitymentioning
confidence: 99%
“…In one study, all types of stroke in patients without atrial fibrillation were included [56]. In one study, BPV was associated with long-term functional outcome independently of, inter alia, stroke subtype (cardioembolic vs. non-cardioembolic) or infarct area (anterior vs. posterior) [52]. In one study, it was shown that BPV did differ between stroke subtypes (anterior circulation, posterior circulation, or lacunar) and therefore they were not included in further analysis [34].…”
Section: Long-term Blood Pressure Variabilitymentioning
confidence: 99%